Mississippian lithofacies and foraminiferal biozonation of the Alborz Mountains, Iran: Implications for regional geology. (8th June 2018) - Zandkarimi, Keyvan; Vachard, Daniel; Najafian, Bahram; Mosaddegh, Hossein; Ehteshami‐Moinabadi, Mohsen
Abstract : The Mississippian rocks at 5 sections, Kalariz, Peyghambaran, Jaban, Naserabad, and Dozdehban, have been measured and sampled in a SE–NW direction across the Alborz Mountains. Foraminiferal zones recognized in those sections, as well as a revision of other foraminiferal assemblage previously published from the Alborz Mountains, allow to recognize 12 biozones: 5 in the Tournaisian: Unilocular (MFZ1–MFZ2? interval), Septabrunsiina krainica (MFZ3–MFZ5 interval), Eotextularia diversa (MFZ6), Darjella monilis (MFZ7), and primitive Eoparastaffella (MFZ8); 5 Viséan biozones: Eoparastaffella simplex (MFZ9), primitive archaediscids (MFZ10), Uralodiscus rotundus (MFZ11), Pojarkovella – Koskinotextularia (MFZ12), Neoarchaediscus (Upper Mikhailovian), Howchinia gibba–Archaediscus/Paraarchaediscus at angulatus‐tenuis stage –Neoarchaediscus akchimensis (Venevian substage); and 2 Serpukhovian biozones: Biseriella parva – Climacammina (Tarusian–Steshevian substages) and Turrispiroides multivolutus–Brenckleina–Eostaffellina protvae (Protvian substage) for the Mississippian rocks of Alborz. Analysis of foraminiferal assemblages indicates a noticeable age difference of the Mississippian rocks between the northern and southern flanks of Alborz. Accordingly, south‐eastern and east‐central Alborz (Kalariz, Peyghambaran, and Jaban sections) display complete Tournaisian deposits (MFZ1–MFZ8), whereas northern Alborz contains the strata dated from Late Tournaisian to Late Serpukhovian (MFZ8–MFZ16). The sedimentological studies also reveal sharp facies variations following the mentioned age variation. Previously, the age variations of these rocks were attributed to various events, such as the Mississippian glaciation phases. However, the age, facies, and thickness variations of lithostratigraphic units in the Alborz are not specific to the Mississippian and are reported during the entire Palaeozoic and even Mesozoic and Cenozoic. They can rather be attributed to the inherited basement and syn‐sedimentary E–W‐trending faults.